2014
DOI: 10.1101/gad.241968.114
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-restricted activity of hnRNPM promotes breast cancer metastasis via regulating alternative splicing

Abstract: Tumor metastasis remains the major cause of cancer-related death, but its molecular basis is still not well understood. Here we uncovered a splicing-mediated pathway that is essential for breast cancer metastasis. We show that the RNA-binding protein heterogeneous nuclear ribonucleoprotein M (hnRNPM) promotes breast cancer metastasis by activating the switch of alternative splicing that occurs during epithelial-mesenchymal transition (EMT). Genome-wide deep sequencing analysis suggests that hnRNPM potentiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
243
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(267 citation statements)
references
References 65 publications
15
243
1
1
Order By: Relevance
“…Recent data indicate that it acts in an opposite way to ESRP1 and is crucial for EMT and metastasis by supporting CD44s splicing. 51 In addition to the antagonistic role of hnRNPM/ESRP1, our data support that EMT-specific splicing is also regulated by qRT-PCR expression analysis of CD44 isoforms at different time-points during a 21-day TGFb treatment of MCF10A cells. Analysis was performed by using specific primers for variants containing sequences encoded by exons v2 to v10.…”
Section: Discussionsupporting
confidence: 63%
“…Recent data indicate that it acts in an opposite way to ESRP1 and is crucial for EMT and metastasis by supporting CD44s splicing. 51 In addition to the antagonistic role of hnRNPM/ESRP1, our data support that EMT-specific splicing is also regulated by qRT-PCR expression analysis of CD44 isoforms at different time-points during a 21-day TGFb treatment of MCF10A cells. Analysis was performed by using specific primers for variants containing sequences encoded by exons v2 to v10.…”
Section: Discussionsupporting
confidence: 63%
“…[26][27][28] Several studies have shown the involvement of various members of splicing kinases, especially SRPKs in multiple cellular processes including proliferation and angiogenesis. 29,30 Overexpression of splicing factors (SRSF1, SRSF2) has been reported in lung, colon and breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer metastasis is a major cause for cancerrelated death in women (Xu et al, 2014), breast cancer metastasis involves the spreading of cancer cells from the primary site to distant sites included lymph node, lungs, liver, bone, and brain. However, the etiology of breast cancer metastasis is unclear and its diagnosis markers are also rare.…”
Section: Discussionmentioning
confidence: 99%